PENGENDALIAN PROGRAM SANITASI LINGKUNGAN BERBASIS MASYARAKAT DI DESA PAMEKARAN KECAMATAN SOREANG KABUPATEN BANDUNG - Lubis, Bella Meutia; Santosa, Pandji (Ilmu Pemerintahan Universitas Langlangbuana, 2023)
This research is driven by a multitude of issues, including the unregulated disposal of wastewater directly into rivers, the absence of clear demarcation between black water and grey water, and the limited awareness within the community regarding the significance of clean and healthy living practices. The theoretical framework employed in this study adheres to the principles of control, as outlined by Mockler in Handoko (2013). These principles encompass the establishment of standards, the measurement of performance, and the implementation of corrective measures. The research methodology utilized is a descriptive research approach with a qualitative orientation. Data for the study were meticulously sourced from a variety of channels, encompassing comprehensive literature reviews, extensive field observations, in-depth interviews, and scrupulous document analysis pertaining to environmental sanitation programs. The research findings unequivocally demonstrate that in the endeavor to exert control over the Community-Based Environmental Sanitation Program in Pamekaran Village, the establishment of standards was pivotal. These standards encompassed the identification of underlying issues, the strategic development of solutions, and the deliberate process of community socialization. Furthermore, in the meticulous assessment of performance achievements, the effectiveness of the program was meticulously scrutinized, areas requiring substantial enhancements were diligently identified, and a cascade of deliberate corrective measures was set in motion. This included the construction of communal Wastewater Treatment Plants (WWTP) and the judicious provision of septic tanks to residents, manifesting as tangible and pragmatic solutions aimed at effecting meaningful improvements.